Comparison of inflammatory cytokine profiles in plasma of patients undergoing otorhinological surgery with propofol or isoflurane anesthesia - Mazoti, Marina Azer [UNESP]; Braz, Mariana Gobbo [UNESP]; Golim, Marjorie de Assis [UNESP]; Braz, Leandro Gobbo [UNESP]; Dias, Norimar Hernandes [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Fecchio, Denise [UNESP] (Springer Nature, 2013)
Objective and design: The effects of anesthetics on cytokine release in patients without comorbidities who undergo minor surgery are not well defined. We compared inflammatory cytokine profiles in adult patients undergoing minimally invasive surgery who received isoflurane or propofol anesthesia. Methods: Thirty-four patients without comorbidities undergoing minor surgery were randomly assigned to receive an inhaled anesthetic (isoflurane; n = 16) or an intravenous anesthetic (propofol; n = 18). Blood samples were drawn before premedication and anesthesia (T1), 120 min after anesthesia induction (T2), and on the first post-operative day (T3). Plasma concentrations of interleukins (IL-) 1β, 6, 8, 10 and 12 and tumor necrosis factor (TNF)-α were measured using flow cytometry. Results: The pro-inflammatory cytokine IL-6 was increased in the isoflurane group at T2 and T3 compared to T1 (P < 0.01). In the propofol group, IL-6 and IL-8 were significantly increased at T3 compared to T1. However, there were no significant differences in cytokine concentrations between the isoflurane and propofol groups. Conclusion: An inflammatory response occurred earlier in patients who received an inhaled agent compared with an intravenous anesthetic, but no differences in plasma cytokine profiles were evident between isoflurane and propofol anesthesia in patients without comorbidities undergoing minimally invasive surgeries. © 2013 Springer Basel.
Keywords: Cytokines; Flow cytometry; Inflammatory response; Isoflurane; Minor surgical procedures; Propofol